Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil. (June 2023) - Mehmood, Sajid; Ahmed, Waqas; Mahmood, Mohsin; Rizwan, Muhammad Shahid; Asghar, Rana Muhammad Ammar; Alatalo, Juha M.; Imtiaz, Muhammad; Akmal, Muhammad; Abdelrahman, Hamada; Ma, Jifu; Ali, Esmat F.; Li, Weidong; et al.
Abstract: Sustainable and safe management of aquaculture sediments is of great concern. Biochar (BC) and fishpond sediments (FPS) are rich in organic carbon and nutrients and thus can be used as soil amendments; however, it is not fully explored how the biochar amended fishpond sediments can affect soil properties/fertility and modulate plant physiological and biochemical changes, particularly under contamination stress. Therefore, a comprehensive investigation was carried out to explore the effects of FPS and BC-treated FPS (BFPS) on soil and on spinach ( Spinacia oleracea L.) grown in chromium (Cr) contaminated soils. Addition of FPS and BFPS to soil caused an increase in nutrients content and reduced Cr levels in soil, which consequently resulted in a significant increase in plant biomass, chlorophyll pigments, and photosynthesis, over the control treatment. The most beneficial effect was observed with the BFPS applied at 35 %, which further increased the antioxidant enzymes (by 2.75-fold, at minimum), soluble sugars by 24.9 %, and upregulated the gene expression activities. However, the same treatment significantly decreased proline content by 74.9 %, Malondialdehyde by 65.6 %, H2 O2 by 65.1 %, and Cr concentration in spinach root and shoot tissues. Moreover, the average daily intake analysis showed that BFPS (at 35 %) could effectively reduce human health risks associated with Cr consumption of leafy vegetables. In conclusion, these findings are necessary to provide guidelines for the reutilization of aquaculture sediments as an organic fertilizer and a soil amendment for polluted soils. However, more future field studies are necessary to provide guidelines and codes on aquaculture sediments reutilization as organic fertilizer and soil amendment for polluted soils, aiming for a more sustainable food system in China and globally, with extended benefits to the ecosystem and human. Graphical abstract: Unlabelled Image Highlights: Rational reuse of aquaculture sediments as fertilizer has been examined in this study. Fishpond sediments (FPS) and biochar treated-FPS (BFPS) improved soil properties. FPS and BFPS increased soil nutrients, plant growth indices, and reduced Cr uptake. BFPS enhanced chlorophyll, antioxidant enzymes, and soluble sugars content in plants. BFPS reduced human health risks associated with Cr consumption of leafy vegetables.